SAT0259 High plasma concentration of mycophenolate acid in early phase of induction therapy predicts good renal outcome in lupus nephritis class iii or iv. (15th June 2017) - Kiyokawa, T; Hanaoka, H; Iida, H; Ishimori, K; Takakuwa, Y; Okazaki, T; Ozaki, S
Abstract : Background: Mychophenolate mofetil (MMF) is recommended as initial induction treatment for most cases of lupus nephritis (LN) class III-IV. Although the association between area under the concentration-versus-time curve (AUC) of myochophenolate acid (MPA) and therapeutic efficacy has been well shown in renal transplantation, it has been poorly investigated in LN. Furthermore, MMF interacts with multiple factors and its concentration may be decreased by high prednisolone (PSL) dose, low serum albumin level and low creatinine clearance. Since these factors dramatically change in induction phase of LN, the plasma concentration of MPA may also change by fixed dose of MMF administration. Here, we measured AUC0–12 of MPA at different phases of induction treatment, early and middle, and prospectively investigated which concentration predicted future renal response in LN class III-IV. Objectives: To investigate the relationship between the plasma concentration of MPA in early or middle phase of induction therapy and future renal response. Methods: We prospectively enrolled patients with biopsy proven LN class III or IV who hospitalized from Apr to Oct 2016. As induction therapy, PSL was started at dose of 1mg/kg/day and tapered to 10mg/day by 12 weeks. Fixed dose of MMF at 2, 000mg/day was continuously introduced. We measured 2 points of MPA plasma concentration depending on the phase of induction therapy, at early (week 2) and middle (week 12). We evaluated the association between these concentration and complete renal response (CR) rate at week 12. Results: Six patients were enrolled. AUC0–12 between the early and the middle phase was not correlated (R 2 =0.17, p=0.7), but that of the early phase tended to be lower (47.4±25.6 vs 58.9±19.1 mgh/L). All the patients with high AUC0–12 (over 40mgh/L) at the early phase achieved CR at week 12 (Figure 1 ). But we could not find any association between AUC0–12 at middle phase and CR rate at week 12. Conclusions: High AUC0–12 of MPA at the early phase of induction therapy might predict good renal response. Disclosure of Interest: None declared